Business strategy design of anthropometric Kit products using SWOT, AHP, and Topsis analysis (Case Study: PT. Sadamaya Graha Teknologi) - Prayitno, Muhamad Agung; Putro, Bramantiyo Eko (Operations Excellence: Journal of Applied Industrial Engineering, 2025)
Public health problems in Indonesia that have a high prevalence are stunting. The high number of stunting cases should be an opportunity to increase sales for PT. SGT as a manufacturer of anthropometry kit products. However, PT. SGT's market share is still not optimal. Therefore, a strategy is needed to increase sales in the next period. The purpose of this study is to analyze the selection of the best strategy for PT. SGT by using a questionnaire that will be distributed to 3 respondents. The data is used to conduct a SWOT analysis and IE matrix to determine the best business strategy, and then other methods such as AHP-TOPSIS are used as support in determining its business strategy. Based on the internal and external matrix (IE) analysis that has been carried out, the anthropometry kit product is located in quadrant I, namely Grow and Build. Several classifications of strategies offered are forward, backward, or horizontal integration, market penetration, market development, and product development. Through analysis using the AHP-TOPSIS method, the best strategy that can be carried out by the company is a market penetration strategy with the indicator of gradually increasing production capacity by collaborating with partners.